Valoración cualitativa del impacto ambiental en una planta productora de aceite de palma en Colombia (2018)
In this work, an environmental impact assessment of a crude palm oil company located in Bar-ranca de Upía (Colombia) was carried out. The research involves the evaluation to the environ-mental aspects and impacts associated with all activities and products of the production process using the methodology proposed by Conesa. Based on the results obtained, the company will be assume the environmental management plan as an integral part of its business strategy in order to contribute to the environmental sustainability.